Circulating MicroRNA as Thrombosis Sentinels: Caveats and Considerations - Tay, Jasmine; Tiao, Jim; Hughes, Quintin; Jorritsma, Jessica; Gilmore, Grace; Baker, Ross (Seminars in Thrombosis and Hemostasis, 2018)
The small noncoding RNAs, microRNAs (or miRNAs), have been implicated in a myriad of diseases and accumulating evidence indicate their potential high value as diagnostic biomarkers. Although their roles in hemostasis and coagulation pathways are less defined, many studies have demonstrated their participation in regulating key factors of hemostasis. However, the mounting challenges associated with the accurate measurement of circulating miRNAs and the involvement of platelet activation in contributing to the circulating miRNA expression profile introduce further complexity to the study of thrombosis-associated miRNAs. This review outlines the current knowledge of miRNAs that have been postulated to regulate key hemostatic factors, and miRNA diagnostic panels in thrombotic disease, with a focus on experimental fundamentals, such as selecting condition-specific reference controls, considerations that are crucial for accurate evaluation of miRNAs in the context of disease biomarkers.
Keywords: microRNAs; thrombosis; circulating miRNAs; miR-494; biomarkers